Aportes de la metodología PMI a la gerencia de Mipymes constructoras en la gestión de proyectos (2017)
This study was carried out with the purpose of investigating the project management methodology of the PMI, specifically the PMBOK guide, for its application in the management of Mipymes constructors. The problem with this investigation was to find the most important aspects of project management and how managers direct these; The search for bibliographic information was carried out and it was confronted with all the aspects found in interviews with three Mipymes managers about how they carry out project management.